Late schizophrenia - V. E. Pashkovskiy (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
Introduction. The problem of late schizophrenia is one of the most controversial in clinicalpsychiatry. The organic factors that accompany the aging process make diagnosis difficult. Based on the consensus statement from an international group of experts in the field, this review discusses the features of schizophrenia in old age with a debut at a young age, late-onset schizophrenia (illness onset after 40 years of age) and very-late-onset schizophrenia-like psychosis (onset after 60 years). Method. The author conducted a study of MEDLINE sources on late schizophrenia.Results.This review provides data on the prevalence, neuroanatomy, pathogenesis, clinical presentation and treatment of schizophrenia in the elderly.Conclusion. Late schizophrenia is becoming a serious public health problem worldwide. Particularly relevant are the problems of the course of the disease, medical care and comorbidity in older psychiatric patients (general and illness-related), and treatment concerns related to the use of antipsychotics